Agonizing GABABR suppresses GLP-1RA’s chronotropic effect and reduces post-myocardial infarction arrhythmogenesis - Qi, Run; Jingjing, Zhang; Hongchang, Gu; Chenyu, Li; He, Hu; Juan, Li; Yuqin, Zhao; Xiaolin, Wu (Frontiers in Pharmacology, 2025)
BackgroundGlucagon-like peptide-1 receptor agonists (GLP-1RAs) have been reported to improve cardiovascular outcomes, potentially through glucose metabolism-independent mechanisms. However, their mechanism of heart rhythm remains controversial.MethodsWe investigated the role of the GABAB receptor (GABABR) in mediating GLP-1RA’s chronotropic and anti-arrhythmic effects in a murine myocardial infarction (MI) model. MI was induced by left anterior descending artery ligation. Cardiomyocyte-specific Gabbr1-knockout (Gabbr1cKO) mice were generated via AAV9-cTnT-Cre delivery to Gabbr1f/f mice. Cardiac sympathetic denervation was achieved by 6-hydroxydopamine (6-OHDA) treatment and sympathectomy. Mechanistic insights were obtained through Western blotting, immunofluorescence, in vivo electrophysiology, and patch-clamp recordings.ResultsGLP-1RA increased the heart rate independent of the sympathetic input, suggesting a cardiac-autonomous mechanism. GABABR activation attenuated GLP-1RA-induced tachycardia, whereas Gabrb1 deficiency exacerbated it. GABABR agonism enhanced resistance to ventricular arrhythmias post-MI in a GLP-1RA-dependent manner. Patch-clamp analysis revealed that GABABR-induced repolarization can be suppressed by semaglutide in a dose-dependent manner, indicating the possible mechanism.ConclusionGABABR activation counteracts GLP-1RA’s chronotropic effects while synergistically enhancing anti-arrhythmic efficacy post-MI, highlighting a novel GABABR/GLP-1R interaction in cardiac electrophysiology.